PENGARUH DOSIS PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Phaseolus radiatus L.) - Murdaningsih Murdaningsih (Agriculture Faculty of Flores University, 2014)
This study aims to determine the effect of NPK Mutiara fertilizer dose on the growth and yield of green beans and determine the optimum dosage of NPK Mutiara fertilizer that can deliver growth and yield optimal green beans. The design used in this study is a randomized block design with treatments used were N0 (without fertilizer NPK NPK 0 kg ha-1 or 0 g plot-1), N1 (NPK fertilizer 125 kg ha-1 or 25 g plot-1), N2 (NPK fertilizer 250 kg ha-1 or 50 g plot-1), N3 (NPK fertilizer 375 kg ha-1 or 75 g), N4 (NPK 500 kg ha-1 or 100 g plot-1). Variable observation in this study was plant height, number of leaves, leaf area, number of pods tan-1 fresh weight stover tan-1, the dry weight of stover tan-1, the dry weight of stover ha-1 dry weight of seed tan-1, heavy ha-1 dry beans, dry weight of 100 seeds. The results showed that treatment of NPK fertilizer dose of 500 kg ha-1 very significant effect on plant height of 27.75 cm, leaf number 8 strands, leaf area 357.78 cm2, Total pods 19.65, fresh weight stover tan-1 96, 25 g, dry weight of stover tan-1 76.00 g, stover dry weight ha-1 19.00 tons, dry weight of seed tan-1 5.36-gram dry weight seed ha-1 1.34 tonnes, the weight of 100 seeds 2.62 gr.